Investigation of the Mechanical Properties of GdBa2Cu3O7−δ Added with Nanosized Ferrites ZnFe2O4 and CoFe2O4 Using Ultrasonic Measurement - Malaeb, Walid (2017)
Recently, there is much interest in studying the effect of nanosized ferrites addition on high- T c superconductors. However, little information is available on the mechanical properties. We have investigated the effect of (CoFe2O4) x and (ZnFe2O4) x nanosized ferrites with 0.01 ≤ x ≤ 0.40 on the mechanical properties of the high- T c superconducting compound GdBa2Cu3O7−δ (Gd-123) prepared by the conventional solid-state reaction technique. Elastic parameters including shear modulus (G), bulk modulus (B), and Young’s modulus (E) of all samples were inspected using ultrasonic measurements and compared with Vickers microhardness results. Furthermore, the porosity of the samples was investigated and correlated to Young’s modulus, which was corrected to zero porosity using different models. The corrected values were correlated with Vickers microhardness. Moreover, the Debye temperature (θ D) and the electron-phonon coupling factor (λ) were also determined as a function of x. We observed that the different nanoparticles addition has influenced the Gd-123 compound differently. For (ZnFe2O4) x added samples, the mechanical properties and Debye temperature improved up to x = 0.06, then deteriorated with further addition. However, (CoFe2O4) x addition improved the mechanical properties for all samples with x up to 0.40. We found that the proportionality constant between the corrected values of E and H v and G and H v are strongly dependent on the porosity corrections and the kind of superconducting material. This indicates that the widely used formula E = 81.96 H v may not be valid for all types of superconducting materials.